Between authority and interpretation on the theory of law and practical reason - Raz, Joseph (Oxford : Oxford University Press, 2009)
Joseph Raz develops his work on some central questions in practical philosophy: legal, political and moral. This text provides an overview of Raz's views on the methodology of jurisprudence; on the nature of law and its relation to morality; on the justification of authority; and interpretation in law and the humanities.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Philosophy; Practical reason; Legal authorities; Law